Appraisal and repair of claddings and fixings - Wilson, M. (Appraisal and repair of buildings structures series., 1993)
This title is a practical guide to the detection and remedy of faults in claddings and fixings on buildings. It sets out the problems involved in common cladding systems for buildings, and relates these problems to all the materials used: stone masonry, concrete and glass-reinforced composites.